Non-Invasive Antibody Assessment in Saliva to Determine SARS-CoV-2 Exposure in Young Children - Heinzel, Constanze; Pinilla, Yudi T.; Elsner, Käthe; Friessinger, Evelyn; Mordmüller, Benjamin; Kremsner, Peter G.; Held, Jana; Fendel, Rolf; Kreidenweiss, Andrea (Frontiers in Immunology, 2021)
Saliva is a body fluid with hitherto unused potential for the assessment of SARS-CoV-2 antibodies. Specific antibodies can indicate a past SARS-CoV-2 infection and allow to estimate the proportion of individuals with a potential protective immunity. First, we carefully characterized plasma samples obtained from adult control groups with and without prior SARS-CoV-2 infection using certified reference ELISAs. Simultaneously collected saliva samples of confirmed convalescent and negative individuals where then used to validate the herein newly developed ELISA for the detection of SARS-CoV-2 IgG antibodies in saliva. The saliva ELISA was applied to assess SARS-CoV-2 exposure in young children (N = 837) in the age between 1 and 10 years in Tübingen, Germany, towards the end of the first pandemic year 2020. Sensitivity and specificity of the new saliva ELISA was 87% and 100%, respectively. With 12% of all Tübingen children sampled via their respective educational institutions, estimates of SARS-CoV-2 antibody prevalence was 1.6%. Interestingly, only 0.4% preschool kids were positive compared to 3.0% of primary school children. Less than 20% of positive children self-reported symptoms within two months prior to saliva sampling that could be associated - but not exclusively - with a SARS-CoV-2 infection. The saliva ELISA is a valid and suitable protocol to enable population-based surveys for SARS-CoV-2 antibodies. Using non-invasive sampling and saliva ELISA testing, we found that prevalence of SARS-CoV-2 antibodies was significantly lower in young children than in primary school children.